Various Neurological Symptoms with Vitamin B12 Deficiency and Posttreatment Evaluation - Arıcan, Pinar (J Pediatr Neurosci, 2020)
BACKGROUND: Vitamin B12 deficiency occurs primarily as a result of insufficient dietary intake in children in developing countries. Vitamin B12 deficiency produces a cluster of neurological symptoms in children. AIM: The aim of this study was to describe the vitamin B12 status of patients who were admitted with neurological symptoms and to evaluate the clinical response to vitamin B12 treatment. MATERIALS AND METHODS: This study was conducted on children who had vitamin B12 deficiency presented with neurological findings from January 2014 to October 2016. Patients with serum vitamin B12 levels lower than 300 pg/mL received intramuscular or oral vitamin B12 treatment. RESULTS: Three hundred and fifty-one patients presenting with neurologic symptoms and who had low serum vitamin B12 deficiency were analyzed. Our study population was composed mainly of adolescent age. The most common symptom with respect to age was headache. In infant patients, most common symptoms were seizure and developmental delay. CONCLUSION: Early diagnosis and vitamin B12 treatment are advocated to avoid long-term injury. Our study shows that patients with serum vitamin B12 levels lower than 300 pg/mL showed clinical improvement of neurological symptoms after receiving vitamin B12 treatment.